Factors that cause anger among motorcyclists: exploratory factor analysis - Sharifah Liew; Rizati Hamidun; Azhar Hamzah (Intelektual Pustaka Media Utama, 2022)
Anger arising while riding a motorcycle is becoming a common problem on the road and it may be caused by many factors. The main objective of this study is to examine factors that could provoke anger among motorcyclists while riding. This study was based on self-reported questionnaires and comprised of 407 motorcyclists who owned valid riding licenses. exploratory factor analysis (EFA) indicated that the sample fit was suitable for factor analysis. In total, eight factors (unsafe or inappropriate actions, rude or sluggish actions, road conditions and design, police or enforces presence, illegal actions on the road, hazards on the road, rainy condition and obstruction on the road) with eigenvalues above 1.0 and 59 variables that ranged from 0.411 to 0.803, were generated. Cronbach’s Alpha analysis indicated that all factors’ values were greater than 0.60 and mean for all factors were reliable and had strength of consistency. This study provides the preliminary findings of factors and variables that could provoke riding anger among motorcyclists while on the road in the Malaysian context. The factors causing riding anger in this study have a similarity with driving anger factors that were developed by other countries and this indicates the validity of riding anger factors to provoke anger among motorcyclists on the road.